The Role Of Boarding School In Improving Public Political Participation In The 2024 Election In Jember District - Nusanto, Baktiawan; Thamrin , Mohammad (Universitas Muhammadiyah Jember Press, 2023)
This study aims to examine the Role of Islamic Boarding Schools in Increasing Community Political Participation in the 2024 Election. In Jember Regency, the Election is an effort to convince and involve individuals in the political process. This is because there are symptoms of decreasing enthusiasm for community members' involvement in the election. The decrease in community enthusiasm is caused by the lack of political influence on the lives of the wider community. Many policies issued by the government are considered misdirected and inappropriate, only certain groups are directly influenced by these policies. Therefore, in the election process, the community is convinced through campaigns to involve the community in the political process and increase enthusiasm in the implementation of the election. The dynamics of political mobilization based on religious identity cannot be separated from the role of religious institutions and religious figures. In this case, the institution in question is the Islamic boarding school or better known as the Islamic boarding school, which is a traditional Islamic religious education and broadcasting institution in Indonesia. Life in Islamic boarding schools has a different cultural and traditional system from the lives of society in general, in Islamic boarding schools the students are educated with binding regulations. Traditional Islamic boarding school (Salafiyah) students tend to be unfamiliar with all forms of problems that are happening outside, because in this case, Salafiyah students are only involved in religious activities in the pesantren environment. Salafiyah students only get religious knowledge without being accompanied by general knowledge. This condition ultimately makes those from Salafiyah Islamic boarding schools emerge as religious leaders, or they will plunge into informal sectors. Along with the development of the times, Islamic boarding schools also have another side of life that is no less important, namely politics, therefore, as we have seen so far that in every important political momentum in the history of the nation, Islamic boarding schools are always involved (Ismail, 1999). The role of Islamic boarding schools today is also very clear. The most obvious example is the difficulty of the government to popularize programs if not through Islamic boarding school leaders. Another example is the number of political leaders approaching Islamic boarding schools, especially before the general election. The behavior of these leaders is right, if they do not approach Islamic boarding school leaders, it means that their political vision is low. The influence of the kiai is not only on the students in his pesantren, but also the community around the pesantren and can even go further. The absolute authority and power possessed by the kiai is often used by political forces (political parties) to gain support from the students and the surrounding community.